Implementation of hair care learning using keratin - Citra Meila Andini; Erna Setyowati; Septi Yuni Rohana (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
The excessive application of chemical agents in bleaching, hair colouring, and straightening can cause damage to the hair shaft, resulting in dryness, coarseness, fluffiness, and frizz. Frizzy hair signifies considerable damage that cannot be sufficiently remedied with standard hair care; hence, it requires additional keratin therapy treatment. Problems arise when university hair care curricula just offer hair mask techniques, whereas the salon industry uses keratin treatments to manage frizzy hair. Although employing different substances, hair mask treatments, and keratin treatments exhibit similar phases and techniques to sophisticated hair treatments. This study examines the implementation of hair mask instruction in universities using keratin treatment techniques in the salon industry. This study aims to evaluate the suitability of including hair care education (hair mask) using the keratin treatment method for frizzy hair in the salon industry. The research utilises a descriptive methodology with a quantitative approach. The data collection approach utilised a questionnaire designed in alignment with the competency standards of hair mask hair care courses. The research participants consisted of 15 Beauty Education students from Semarang State University, representing the 2022 and 2023 cohorts, who were employed in salons. A quantitative descriptive analysis employing percentages was performed for data analysis. The analysis of hair damage indicators yielded a score of 85%, deemed very suitable; the preparation of hair care tools and materials achieved 88%, also classified as very suitable; hairdressing techniques received a score of 79%, categorised as appropriate; mask application and infiltration techniques attained 82%, classified as appropriate; and drying, styling, and results techniques were rated at 75%, categorised as appropriate.